2014
DOI: 10.1097/jnr.0000000000000028
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Older Residents With Stroke Living in Long-Term Care Facilities

Abstract: Healthcare providers should conduct depression screening for elderly residents with stroke on admission to long-term care facilities. Regular assessment and monitoring of depressive symptoms, especially in residents with less formal education and limited physical functions, are important in nursing homes and intermediate-care facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…One Taiwanese study indicated that the prevalence of depressive symptoms (36.9%) in older residents who had experienced a stroke was similar to the findings of this study (Huang et al, ). However, three studies conducted in Taiwan revealed higher prevalence of depressive symptoms among residents—81.8% (Lin et al, ), 52.05% (Lin et al, ), and 49% (Tsai, )—than the prevalence found in the current study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…One Taiwanese study indicated that the prevalence of depressive symptoms (36.9%) in older residents who had experienced a stroke was similar to the findings of this study (Huang et al, ). However, three studies conducted in Taiwan revealed higher prevalence of depressive symptoms among residents—81.8% (Lin et al, ), 52.05% (Lin et al, ), and 49% (Tsai, )—than the prevalence found in the current study.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the prevalence of depression or depressive symptoms is higher in older adults living in LTCFs than in those living in the community, with approximately 19.0% in Canada (McCusker et al, ), 21.1% in Singapore (Tiong, Yap, Huat Koh, Phoon Fong, & Luo, ), 21.6% in the United States (Hoover et al, ), 27.1% in England and Wales (McDougall et al, ), 74% in Poland (Kowalska, Bojko, Szczepanska‐Gieracha, Rymaszewska, & Rozek‐Piechura, ), and 90.2% in Iran (Nazemi et al, ). In Taiwan, the prevalence of depression or depressive symptoms in LTCFs is also remarkable with reports of 36.9% and 81.8% of older residents having experienced depressive symptoms in LTCFs (Huang et al, ; Lin, Wang, & Huang, ). However, the prevalence of depressive symptoms or depression in older LTCF residents with intact cognitive function is still poorly understood, except for one study conducted in Norway (Drageset, Eide et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…The prevalence of depressive symptoms or depression in long‐term care facilities (LTCFs) is high regardless of whether in Taiwan (36.3%–81.8%) (Huang et al . ; Lin et al . ) or other countries (47.4%–90.2%) (Kowalska et al .…”
Section: Introductionmentioning
confidence: 99%
“…Demographic factors such as age, gender, marital status, religion and faith, educational level, occupation, economic status, living patterns, hospitalization duration, and changed environment are all related to depression in elderly people [1,7,8,11]. Physical factors such as acute myocardial infarction, heart failure, stroke, cerebrovascular accident, hypothyroidism, crippling and/or disabling diseases, dementia and neurodegenerative diseases, bone fractures, osteoporosis, arthritis, and chronic illness; dysfunction in physical attributes, such as blood sugar and cardiovascular system imbalance, hydroelectrolytic disturbances, or lower liver and kidney functions; and lower daily activity score are related to depression in elderly people [1][2][3]6,7,10].…”
Section: Related Factors Of Depression In Elderly Peoplementioning
confidence: 99%
“…Studies have shown that currently, 30% of elderly people aged more than 65 years have emotional disorders, and 64% of hospitalized elderly people have depression symptoms such as low mood, sleep disturbance, poor appetite, or pain combined with anxiety [1][2][3][4][5]. Additionally, 36.9% of 111 elderly patients experienced depression, and the prevalence was 45.7%, 36.2%, and 22.2% in those living in nursing homes, intermediate care facilities, and domiciliary care facilities, respectively [6]. Specifically, 21.7% of 152 veterans developed depression [7].…”
Section: Introductionmentioning
confidence: 99%